The enhanced antifungal effect against Pyricularia oryzae of Cu nanoparticles/chitosan supplemented with ammonium soap synthesised from palm oil - Tuan Nghiem Anh Le; Nghi Tran; Nhung Hong Nguyen; Tho Phuoc Tran; Giang Ngoc Doan; Ngoc Thanh Truong; Du Duy Bui (Vietnam Journal of Science, Technology and Engineering)
This study reports the preparation method of ammonium soap (AS) from palm oil and NH4OH solution, in combination with chitosan-coated copper nanoparticles (CuNPs/CS), to enhance antifungal efficacy (AE) against Pyricularia oryzae, the causal agent of rice blast disease. The properties of AS, including the saponification reaction efficiency, pH, and its ability to reduce the surface tension of water, were also investigated. The CuNPs/CS nanocomposite was synthesised using N2H4 as a reducing agent for Cu²+ in solution. The resulting CuNPs exhibited a size of 17.9±3.4 nm, as determined by transmission electron microscopy (TEM) images. Ultraviolet-visible (UV-Vis), X-ray diffraction (XRD), and Fourier-transform infrared (FTIR) analyses confirmed the formation of CuNPs in the CS solution. The in vitro AE of CuNPs/CS against in vitro reached 100% at a Cu concentration of 30 mg/l. When 0.05% AS was added to the CuNPs/CS, the AE reached 100% at a Cu concentration of 25 mg/l. Notably, in vivo experiments demonstrated that spraying CuNPs/CS at a Cu concentration of 25 mg/l with 0.05% AS resulted in significantly higher rice blast control efficiency compared to spraying CuNPs/CS at 30 mg/l Cu concentration (86.91 vs 71.32%). AS supplementation was considered a promising approach to enhancing the activity of CuNPs/CS in controlling rice blast disease caused by P. oryzae.